Assessment of effective communication on patient treatment identity card use at the center for lung health community Makassar City - Muhammad Thabran Talib; Hidayati Hidayati; Musmulyadi Musmulyadi; Bahtiar Bahtiar (Universitas Aisyah Pringsewu, 2023)
As a health service facility that provides a place used to organize health service efforts. With various duties of the Community Lung Health Center is to carry out the functions of its parent organization, through the implementation of health efforts. The purpose is to find out the effective communication assessment of the use of patient treatment identity cards at the Makassar Community Lung Health Center. Results, Communication Assessment of Identity Cards for Treatment on Information Clarity with excellent rating of 84.92%, Speed of registration with excellent rating of 86.22%, Patient Satisfaction with excellent rating of 87.48%, and Service Performance of Medical recording personnel showed excellent assessment of 86.20%. Discussion, health services are one of the important activities carried out with effective communication, especially when receiving patients through the use of Medical Identity Cards so that their use can be used as a form of clarity of useful health service information, can also provide registration speed and produce patient satisfaction and better performance of medical recording personnel. In conclusion, the use of the Patient Treatment Identity Card through the assessment of effective communication gets excellent assessment results from the results of patient treatment and the performance of medical recording personnel services through the form of communication results in an excellent assessment of the clarity of information, speed of service and patient satisfaction. Suggest, improve and maintain the form and pattern of effective communication between the medical recorder and the patient, uphold attitudes, behaviors and actions with good and correct communication and speech of language and sentences to the patient, perpetuate the value and way of communication of health services. Abstrak: Sebagai fasilitas pelayanan kesehatan yang menyelenggaran tempat yang digunakan untuk menyelenggarakan upaya pelayanan kesehatan. Dengan berbagai tugas Balai Kesehatan Paru Masyarakat adalah melaksanakan sebagaian fungsi dari organisasi induknya, melalui penyelenggaraan upaya kesehatan. Tujuan, diketahuinya penilaian komunikasi efektif terhadap penggunaan Kartu Identitas Berobat pasien di Balai Besar Kesehatan Paru Masyarakat Makassar. Hasil, Penilaian Komunikasi terhadap Kartu Identitas berobat pada Kejelasan Informasi dengan penilaian sangat baik 84,92%, Kecepatan pendaftaran dengan penilaian sangat baik 86,22%, Kepuasan Pasien dengan penilaian sangat baik 87,48%, dan Kinerja Pelayanan Tenaga perekam medis menunjukkan penilaian sangat baik 86,20%. Pembahasan, pelayanan kesehatan merupakan salah satu kegiatan penting yang dilakukan dengan komunikasi secara efektif khususnya pada saat penerimaan pasien melalui penggunaan Kartu Identitas Berobat sehingga pemanfaatannya dapat dijadikan sebagai bentuk kejelasan informasi pelayanan kesehatan yang berguna, juga dapat memberikan kecepatan pendaftaran dan menghasilkan kepuasan pasien dan kinerja tenaga perekam medis dapat lebih baik. Simpulan, penggunaan Kartu Identitas Berobat Pasien melalui penilaian komunikasi efektif tersebut mendapatkan hasil penilian sangat baik dari hasil persponden pasien dan kinerja pelayanan tenaga perekam medis melalui bentuk komunikasi menghasilkan penilaian sangat baik terhadap kejalasan informasi, kecepatan pelyanan dan kepuasan pasien. Saran, meningkatkan dan mempertahankan bentuk dan pola komunikasi efektif antara perekam medis dengan pasien, menjunjung tinggi sikap, perilaku dan tindakan dengan komunikasi dan tutur bahasa dan kalimat yang baik dan benar kepada pasien, mempertahakan nilai dan cara komunikasi pelayanan kesehatan.